Analysis of Product Quality, Price Perception, and Promotion on Samsung Smartphone Purchasing Decisions - Cahyaningrum, Diyah Ayu; Santoso, Joko (International Journal of Economics and Business Management, 2025)
This study aims to find out and analyze the effect of product quality, price perception, and promotion on consumer buying decisions in the context of Samsung smartphones. The research was conducted at CM Mobile Mranggen counter. The study uses four variables: product quality, price perception, promotion, and buying decision. The population consists of all consumers who have ever bought a Samsung smartphone at CM Mobile Mranggen, with a sample size of 96 respondents. The sample was selected using non-probability sampling with purposive sampling technique. Data was collected through a questionnaire that had been tested for validity and reliability. The analysis method used in this study is multiple regression analysis, carried out using IBM SPSS 25. The results of this study show that product quality has a positive effect on buying decisions, price perception has a positive effect on buying decisions, and promotion also has a positive effect on buying decisions.